Understanding men’s attitude and perceptions towards women’s education: A cross-sectional study - Imran Jamil (Journal of Peace, Development and Communication, 2022)
The study was design to understand men’s attitude and perceptions towards women’s education. The study was conducted in District Nankana Sahib, Punjab Pakistan. Through multistage sampling total 90 respondents were selected. An interview schedule was used to collect data, and statistically analyzed. Gamma and chi-square tests were applied. So, it is concluded that people are given preference of their males for attaining education as compare to females and the major reason behind this, males support their parents. A big hurdle faced by the female in the study area was "Distance" because schools are far away from their household. The gamma value shows that aged people, illiterate and low-income respondents preferred male education as compare to female. Therefore, it will be recommended that adult literacy initiatives should be implemented in rural areas. It is important to use the mass media to raise awareness of the advantages of female education and the importance of family.